Food services and the importance of food safety: a review - DUTRA, Izidy Christina Rodrigues; ALMEIDA, Raiane Priscila de (130, 2022)
The change in eating habits by the population is notorious, and eating outside the domicile has become a routine for many citizens. New forms of food service also emerged, such as food trucks and delivery, which bring ease and agility in the food service. The work aims to analyze and point out the procedures that these companies apply in their activities, making a more comprehensive comparison of how GMP are practiced and highlighting the training of employees so that they are carried out in the best possible way.

RESUMO: A mudança nos hábitos alimentares da população é notória, e a alimentação fora do domicílio tornou-se uma rotina para muitos cidadãos. Novas formas de food service também surgiram, como food trucks e delivery, que trazem facilidade e agilidade no serviço de alimentação. O trabalho visa analisar e apontar os procedimentos que essas empresas aplicam em suas atividades, fazendo um comparativo mais abrangente de como são praticadas as BPF e destacando o treinamento dos funcionários para que sejam realizadas da melhor forma possível.
Serviços de alimentação e a importância da segurança alimentar: uma revisão
Artigo científico válido como TCC.
Keywords: Serviços de alimentação; Higiene de alimentos; Manipulação de alimentos; Produção Alimentícia